Seismic Reflection Profiles and Subsurface Geology of the Area Interested by the 2016–2017 Earthquake Sequence (Central Italy). Issue 4 (20th April 2018) - Porreca, M.; Minelli, G.; Ercoli, M.; Brobia, A.; Mancinelli, P.; Cruciani, F.; Giorgetti, C.; Carboni, F.; Mirabella, F.; Cavinato, G.; Cannata, A.; Pauselli, C.; et al.
Abstract: Starting from 24 August 2016, a long seismic sequence, including nine Mw  > 5.0 earthquakes, struck a wide area of the Central Italy. A large amount of geological, geodetic, and seismological data envisages a complex system of NNW‐SSE trending, seismogenic normal faults. These active tectonic structures are well known at the surface and consistent with previous seismotectonic studies. In order to improve the comprehension of the seismotectonic framework of this seismic sequence, we provide a novel reconstruction of the subsurface geology of the area close to the Norcia Mw 6.5 mainshock (30 October 2016), based on previously unpublished seismic reflection profiles and available geological data. All the data have been synthesized along a 47 km long, WSW‐ENE trending geological cross section, interpreted down to a depth of 12 km. Comparing the subsurface geological model with the available seismological data, we find that the majority of seismicity is confined within the sedimentary sequence and does not penetrate the underlying basement. The basement has been constrained at depths of 8 to 11 km and coincides with the cutoff of the seismicity. We have also traced the trajectories of the seismogenic normal faults activated during this seismic sequence, reconciling the high‐angle (dip>65°) normal faults exposed at the surface, with their angle (dip < 50°) at hypocentral depths. The results of this study may be useful for better understanding the rheological properties of the seismogenic rock volume, as well as the coseismic deformations of the topographic surface observed by geodetic techniques and field mapping. Plain Language Summary: The 2016–2017 seismic sequence of the Central Italy has attracted many researchers specialized in different topics of Earth Sciences. An impressive amount of data have been collected by these researchers from field geological to deep seismological data. Despite the large number of data, a reconstruction of the deep structures from the surface to the hypocenter depths of the earthquakes is still lacking. Here we present a new geological reconstruction thanks to the interpretation of seismic data kindly provided by the Italian oil company (Eni). Even if these data have been acquired with different aims, they prove to be of great support in seismotectonic research, since the targets of oil explorations are typically located at a depth that is similar to that of the seismogenic sources. Our results confirm that seismic reflection profiles can give important insights on the subsurface geology of the seismically active areas and on the geometry of the seismogenic faults. We have identified the geometry of the main faults related either to the old compressive tectonics, responsible of the formation of the Apennines, and to the most recent extensional seismogenic tectonics. Key Points: The seismic data set provides new constraints on the subsurface geology of the area affected by the 2016–2017 earthquake in Central Italy The main reflector below the Norcia area corresponds to the top of the acoustic basement and coincides with the cutoff of the seismicity The seismogenic normal faults have steep dip angles (65°–70°) close to the surface and lower (45°–50°) at hypocentral depths